2015
DOI: 10.1093/humrep/dev239
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and effectiveness of unintended pregnancy prevention with low-dose mifepristone combined with misoprostol before expected menstruation

Abstract: Menstrual regulation with low-dose mifepristone and misoprostol at expected menstruation can be efficacious and highly acceptable to maintain or restore non-pregnant status, which may have potential for routine contraception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…24 Unscheduled reattendance, a particular concern related to self-administration, was infrequent, and the rate did not differ between groups, consistent with the report that selfadministration of a medical abortion regimen did not increase the unscheduled reattendance rate. 22 Based on the results of the present study in 2015-along with low-dose mifepristone (50 mg) and misoprostol (200 mg) at the time of expected menstruation being under the supervision of professional doctors 23 -we now suggest that the use of low-dose mifepristone (75 mg) and self-administered misoprostol (400 mg) is highly acceptable for ultra-early medical abortion.…”
Section: Safety and Feasibility Of Self-administration Of A Low-dose Medical Abortion Regimenmentioning
confidence: 61%
See 1 more Smart Citation
“…24 Unscheduled reattendance, a particular concern related to self-administration, was infrequent, and the rate did not differ between groups, consistent with the report that selfadministration of a medical abortion regimen did not increase the unscheduled reattendance rate. 22 Based on the results of the present study in 2015-along with low-dose mifepristone (50 mg) and misoprostol (200 mg) at the time of expected menstruation being under the supervision of professional doctors 23 -we now suggest that the use of low-dose mifepristone (75 mg) and self-administered misoprostol (400 mg) is highly acceptable for ultra-early medical abortion.…”
Section: Safety and Feasibility Of Self-administration Of A Low-dose Medical Abortion Regimenmentioning
confidence: 61%
“…4,5 Our 2015 study showed that menstrual regulation with low-dose mifepristone (50 mg) and misoprostol (200 mg) at the expected time of menstruation was efficacious and highly acceptable for the maintenance or restoration of nonpregnant status and may have potential for routine contraception. 23 As the fields of general practice and family medicine are often only in the beginning stages of development, the amount of supervision required for medical abortion, especially ultra-early pregnancy termination, remains a matter of debate. 10 A highly effective, safe, and simplified medical abortion regimen for general practice or self-administration is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors showed that dose of mifepristone could reduce on 200mg and it could reach the same effects as with a dose of 600mg (15,16,17,18,19,20,21). After that it was turned out that the vaginal application of misoprostole was more effective than peroral drug aplication, specially in pregnancy age between 50-63 days gestation (22,23,24).…”
Section: Mifepristone and Misoprostolementioning
confidence: 98%
“…The success rate of abortion for mifepristone-misoprostol regimen is 95-98%. [41], while 78-90% for misoprostol only [42]. Despite highly restrictive abortion laws in LAC, access to safer abortion increased.…”
Section: Medical Terminationmentioning
confidence: 99%